An ultralight, elastic, cost-effective, and highly recyclable superabsorbent from microfibrillated cellulose fibers for oil spillage cleanup1. Issue 16 (28th April 2015) - Wang, Sha; Peng, Xinwen; Zhong, Linxin; Tan, Jiewen; Jing, Shuangshuang; Cao, Xuefei; Chen, Wei; Liu, Chuanfu; Sun, Runcang
<x xml:space="preserve">Abstract</x> An ultralight, elastic, cost-effective, and highly recyclable superabsorbent was fabricated from microfibrillated cellulose fibers for oil spillage cleanup.